Endocan as a marker of disease severity in pulmonary thromboembolism - Kuluozturk, Mutlu; In, Erdal; Ilhan, Nevin (Wiley, 2019)
Introduction The aim of this study is to determine the serum endocan levels in patients with pulmonary thromboembolism (PTE) and investigate whether a relationship exists between serum endocan levels and the disease severity. Materials and Methods The study included 85 patients with acute PTE and 40 healthy control subjects. The patients with PTE were divided into three groups at admission as high-risk, intermediate-risk and low-risk, considering the guidelines of the European Society of Cardiology. Serum endocan levels in all participants' blood samples were measured. Results The mean serum endocan levels were significantly higher in the PTE group, compared to the control subjects (P < 0.001). Serum endocan levels were significantly higher in the high-risk group when compared with patients in the low-risk and intermediate-risk groups (P P < 0.01 respectively). Similarly, serum endocan levels were higher in the intermediate-risk group compared to those in the low-risk group (P < 0.001). There was a negative correlation between serum endocan levels and partial oxygen pressure (r = -0.262, P = 0.016), whereas a positive correlation was found between the serum endocan levels and systolic pulmonary arterial pressure (r = 0.296, P = 0.006). Additionally, endocan had an area under the curve in the receiver operating characteristic curve of 0.837 (0.768-0.907; 95% CI; P < 0.001) and cut-off value was 194.5 pg/mL (sensitivity 80%, specificity 72.5%). Conclusion Serum endocan levels were higher and related to the severity of the disease in PTE patients. Additionally, endocan could be an indicator to be used in the diagnosis of PTE and in the prediction of the disease severity.
Keywords: biomarker; endocan; endothelial cell-specific molecule-1; endothelial dysfunction; pulmonary thromboembolism; right ventricular dysfunction